An Enantiomer of an Oral Small-Molecule TSH Receptor Agonist Exhibits Improved Pharmacologic Properties - Neumann, Susanne; Padia, Umesh; Cullen, Mary Jane; Eliseeva, Elena; Nir, Eshel A.; Place, Robert F.; Morgan, Sarah J.; Gershengorn, Marvin C. (Frontiers in Endocrinology, 2016)
We are developing an orally available small molecule, allosteric TSH receptor (TSHR) agonist for follow up diagnostics of patients with thyroid cancer. The agonist C2 (NCGC00161870) that we have studied so far is a racemic mixture containing equal amounts of two enantiomers, E1 and E2. As enantiomers of many drugs exhibit different pharmacologic properties, we assessed the properties of E1 and E2. We separated the two enantiomers by chiral chromatography and determined E2 as the (S)-(+) isomer via crystal structure analysis. E1 and E2 were shown to bind differently to a homology model of the transmembrane domain of TSHR in which E2 was calculated to exhibit lower binding energy than E1 and was therefore predicted to be more potent than E1. In HEK293 cells expressing human TSHRs, C2, E1, and E2 were equally efficacious in stimulating cAMP production, but their potencies were different. E2 was more potent (EC50 = 18 nM) than C2 (EC50 = 46 nM) which was more potent than E1 (EC50 = 217 nM). In primary cultures of human thyrocytes, C2, E1, and E2 stimulated increases in thyroperoxidase mRNA of 92-, 55-, and 137-fold and in sodium-iodide symporter mRNA of 20-fold, 4-fold and 121-fold above basal levels, respectively. In mice, C2 stimulated an increase in radioactive iodine uptake of 1.5-fold and E2 of 2.8-fold above basal level, whereas E1 did not have an effect. C2 stimulated an increase in serum T4 of 2.4-fold, E1 of 1.9-fold, and E2 of 5.6-fold above basal levels, and a 5 day oral dosing regimen of E2 increased serum T4 levels comparable to recombinant human TSH (rhTSH, Thyrogen®). Thus, E2 is more effective than either C2 or E1 in stimulating thyroid function and as efficacious as rhTSH in vivo. E2 represents the next step toward developing an oral drug for patients with thyroid cancer.